Concurrent BRAFV600E and BRCA Mutations in MSS Metastatic Colorectal Cancer: Prevalence and Case Series of mCRC patients with prolonged OS. (2022) - Cannon, Timothy Lewis; Randall, Jamie N; Sokol, Ethan S.; Alexander, Sonja M.; Wadlow, Raymond C.; Winer, Arthur A.; Barnett, Daniel M.; Rayes, Danny L.; Nimeiri, Halla S.; McGregor, Kimberly A.
Highlights: BRAF mutated CRC is generally understood and treated as a single entity, our team made the observation concurrent HRD mutations seemingly have better outcomes. We found that co-occuring BRAF and BRCA1/2 mutations occur in 0.6% of CRC. This may represent a unique subset of advanced MSS CRC that has a better prognosis that other BRAF mutated CRC. Abstract: Background: BRAF V600E+ microsatellite stable (MSS) metastatic colorectal cancer (mCRC) patients comprise up to 10% of advanced CRC. They have a poor prognosis with a median survival typically <1 year. Despite use of multi-agent 1 st line chemotherapy regimens and combination targeted therapies, outcomes are still poor. In our Institutional Molecular Tumor Board (MTB) database, we identified 3 mCRC patients with MSS/ BRAF V600E who also had a BRCA1 or BRCA2 co-mutation and had relatively long overall survivals. Prior studies suggested that BRCA mutations are uncommon in CRC and we queried the Foundation Medicine (FM) genomic database to evaluate the prevalence of these cases as well as those with co-mutations in other homologous recombination genes. Methods: 36, 966 CRC pts were sequenced by FMI using hybrid capture comprehensive genomic profiling (CGP) to evaluate all classes of genomic alterations (GA) for pathogenic BRAF mutations and/or a mutation in BRCA1/2 or a co-mutation in other homologous recombination (HR) genes ( BARD1, CDK12, FANCL, PALB2, ATM, RAD54L, CHEK2, BRAF, BRIP1, RAD51D, RAD51C, RAD51B, CHEK1 ). Selected cohort analysis of BRAF V600E co-mutated with BRCA1 and BRCA2 were separated into MSI-H and MSS cohorts. The clinicopathological features and genomic loss of heterozygosity (gLOH) of those with a BRAF V600E and a BRCA1/BRCA2 mutation were collected and analyzed. We also describe 3 consecutive cases of mCRC patients, identified through the Inova Schar Cancer Institute (ISCI) MTB registry, whom had prolonged OS. Results: Of 36, 966 colorectal cancer pts, 6.6% were BRAF V600E+ and 1.5% had any co-occurring HR gene mutation(s) with 0.6% of the total mCRC population having co-ocurring BRAF V600E and BRCA1/2 alterations. BRCA co-mutations were higher in MSI-High BRAF V600E, however 24.1% of co-occurrences were observed in MSS samples. BRCA1 co-mutation was more commonly associated with MSS BRAF V600E and was associated with a higher gLOH than MSI-H BRAF V600E (18.7% vs 2.8%; p <0.001). In our institutional MTB database, (3/241;1.2%) CRC patients were MSS, BRAF V600E+ with BRCA1 or BRCA2 co-mutations, all somatic in origin, with an average gLOH of 21.4% and overall survivals of 72+(alive), 17+(alive), and 30 months, respectively. Conclusion: Co-existence of BRAF V600E/ BRCA1/2 may represent a unique subset of advanced MSS CRC that may have a better prognosis and represent an opportunity to test novel targeted therapies. The elevated gLOH in these cases may also be a valuable biomarker for these pts. Larger prospective clinical validation trials in this subset is warranted.